The Effect of Daily Meditative Practices Based on Mindfulness and Self-Compassion on Emotional Distress under Stressful Conditions: A Randomized Controlled Trial - María Elena Gutiérrez-Hernández; Luisa Fernanda Fanjul Rodríguez; Alicia Díaz Megolla; Cristián Oyanadel; Wenceslao Peñate Castro (MDPI AG, 2023)
Intervention programs based on self-compassion have demonstrated their efficacy both in reducing psychological distress and increasing well-being. The goal of this study was to test the efficacy of an online intervention to increase mindfulness and self-compassion levels in a non-clinical sample in a highly stressful context: the ten weeks of lockdown imposed in the early stages of the COVID-19 pandemic. The intervention sessions consisted of thirty-minute guided meditations followed by thirty minutes of inquiry. Sixty-one participants completed two thirds of the sessions or more, and 65 individuals participated in a waiting-list (WL) control group. Self-compassion, anxiety, depression and stress levels were assessed. The analysis of pre-post results suggests that the interventions increased self-compassion levels and decreased anxiety, depression and stress levels, whereas the WL group did not show any significant changes. The emotional changes in the intervention group were associated with the increase in self-compassion. However, at follow-up, the scores of emotional distress variables returned to the initial pre-intervention scores. These data can be interpreted in line with previous results that have shown the efficacy of self-compassion-based intervention programs. Given that this efficacy was not maintained at follow-up, data are discussed according to the pervasive role of a highly stressful context and-as described in other studies-the need for regular practice to maintain the benefits obtained.